Psychology of the heart - Shen, Heyong; Escamilla, Michael (College Station : Texas A&M University Press, 2023)
"The symbol of the heart is at the core of traditional Chinese psychology and culture, according to author Heyong Shen. In this latest volume arising from the popular Fay Lecture Series, sponsored by the Jung Center, Houston, the noted Chinese analyst, scholar, and educator discusses Jungian analysis in China and explores what the historical Chinese emphasis on the heart can add to Western understandings of modern depth psychology. C.G. Jung had a profound personal interest in Chinese culture and wrote extensively on Chinese philosophy and symbolism. In his foreword to Richard Wilhelm's translation of the I Ching, the ancient Chinese oracle and book of wisdom, Jung referred to Chinese logograms as readable archetypes. Continuing this theme, Shen states in his prologue, "Most of the basic psychological terms in Chinese characters are formed originally with the image of the heart and contain deep meaning for the understanding of depth psychology and Jungian analysis ... The Chinese characters for 'thinking,' 'emotion,' 'will,' and 'intention' are all combined with the image of the heart, as are the characters for 'love,' 'hate,' 'compassion,' 'virtue,' 'listening,' 'healing,' and for 'wise,' 'wisdom,' and 'enlightenment.'" The heart serves as the foundation. Drawing from centuries-deep wells of Chinese, Buddhist, and Confucian thought as well as an intimate understanding of the development of Jung's theories, Shen offers a valuable reminder of the many commonalities among humans from all nations as they seek greater levels of self-awareness"--
Origin: The Core, the Seed, and the Heart -- The Heart Method: Wisdom from the Heart -- Readable Archetypes: The Meaning of the Heart Image -- Epilogue -- APPENDIX A. Why The Red Book Is Red: Red, New, and the Heart -- A Red Book Reflection -- APPENDIX B. Fay Lectures 2018: An Interview with Heyong Shen / by Michael Escamilla.
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Psychoanalysis and culture -- China; Jungian psychology -- China; Heart -- Symbolic aspects -- China; Heart -- Psychophysiology; Archetype (Psychology); Psychologie analytique -- Chine; Cœur -- Psychophysiologie; Archétype (Psychologie); Archetype (Psychology); Heart -- Psychophysiology; Heart -- Symbolic aspects; Jungian psychology; Psychoanalysis and culture; China